2016
DOI: 10.1259/bjr.20160648
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a template-based algorithm for markerless lung tumour localization on single- and dual-energy kilovoltage images

Abstract: Objective: To evaluate a template-based matching algorithm on single-energy (SE) and dual-energy (DE) radiographs for markerless localization of lung tumours. Methods: A total of 74 images from 17 patients with Stages IA-IV lung cancer were considered. At the time of radiotherapy treatment, gated end-expiration SE radiographs were obtained at 60 and 120 kVp at different gantry angles (33°anterior and 41°oblique), from which soft-tissue-enhanced DE images were created. A template-based matching algorithm was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 49 publications
(57 reference statements)
1
14
0
Order By: Relevance
“…These values are consistent with a previous study by Block et al. 27 In their study based on images from 17 patients, it was determined that the false positive rate was 20.9% (PSR < 3) versus 4.0% (PSR ≥ 3; P <.01). It is important to note that Block et al results were based on clinical images that were obtained sequentially and processed offline.…”
Section: Discussionsupporting
confidence: 92%
“…These values are consistent with a previous study by Block et al. 27 In their study based on images from 17 patients, it was determined that the false positive rate was 20.9% (PSR < 3) versus 4.0% (PSR ≥ 3; P <.01). It is important to note that Block et al results were based on clinical images that were obtained sequentially and processed offline.…”
Section: Discussionsupporting
confidence: 92%
“…The WLS technique used in conjunction with DE imaging has been shown to improve tumor localization 5,[16][17][18] and enhance performance of MTT methods 4,8,[19][20][21] by suppressing bony anatomy. Conventionally, soft tissue images are created by reducing the contrast of the bone and neighboring soft tissue region followed by assigning a global weighting factor across the image.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of this peak relative to NCC values away from the peak, called side lobe values, is quantified by the peak‐to‐side lobe ratio (PSR). Block et al showed that PSR values can be used as a predictor of successful template matches, and PSR > 3 can reduce the false detection rate …”
Section: Methodsmentioning
confidence: 99%
“…The PSR score is related to the strength of template matching algorithm . For each iteration, the normalized cross‐correlation (NCC) between template and image was computed to produce a 2D match score surface.…”
Section: Methodsmentioning
confidence: 99%